التحليل المكاني للنشاط التجاري لشارع كرادة داخل في بلدية الكرادة (Journal of the College of Basic Education, 2026)
The study aims to identify the main commercial activities and patterns present along “Karrada Dakhel” Street within the Karrada Municipality, and to analyze their efficiency in meeting the needs of local residents and surrounding areas for goods and services. The importance of the study stems from the fact that the street is considered one of the most prominent commercial axes in the city of Baghdad, witnessing a high density of diverse commercial activities that directly impact the city’s urban function. The study adopts a descriptive-analytical approach, supported by field surveys. The results revealed disparities in the distribution and efficiency of commercial activities, with certain types being concentrated at the expense of others, which affected the quality of services provided. The research concluded with a set of recommendations calling for the reorganization of the commercial function along the street to enhance its efficiency and achieve balance and integration in the distribution of various activities.